Process parameters optimization for maximizing tensile strength in friction stir-welded carbon steel - Bhatia, Anmol (Strojniški vestnik, 2021)
The present study focuses on improving the ultimate tensile strength of friction stir welded carbon steel (AISI 1018). The effect of the process parameters (welding speed, tool RPM, and shoulder diameter) on the response parameters (ultimate tensile strength, percentage elongation and percentage reduction in area) were studied. Response surface methodology was used to develop the mathematical model for response parameters, and the adequacy of the model was checked using analysis of variance (ANOVA). The welding speed and tool RPM were found to affect the ultimate tensile strength significantly. The percentage elongation was affected only by welding speed. The percentage reduction in the area was affected by welding speed and shoulder diameter. The microstructure and microhardness of the weld have been studied and reported in the study.
Keywords: ANOVA; friction stir welding; jeklo; metoda odzivnih površin; microhardness; microstructure; mikrostruktura; mikrotrdota; morfologija loma; porušitvena natezna trdnost; response surface methodology; steel; torno varjenje z gnetenjem; ultimate tensile strength